Solid-phase microextraction of aliphatic aldehydes C5–C8 and gas chromatographic determination for lung cancer diagnosis - Zakharkiv, I. B.; Zui, M. F. (Reports of the National Academy of Sciences of Ukraine, 2016)
A headspace solid-phase microextraction procedure followed by gas chromatography with flame ionization detection has been developed for the preconcentration and the determination of aliphatic aldehydes C5−C8 in the form of its o-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine derivatives in water samples. Commercial polydimethylsiloxane-divinylbenzene fiber was used as a preconcentration coating. Under optimal conditions, the enrichment factors of analytes were in the range 7280–8650, and the limits of detection were 0.016–0.020 μM/L.